INFLUENCE OF HYDROCARBON COMPOSITION OF NAPHTHA FEED ON THE YIELD AND OCTANE NUMBER OF REFORMATE - A.S. Nasution (Scientific Contributions Oil and Gas, 2004)
The rapidly increasing demand for high octane num- ber gasoline and aromatic hydrocarbon as a petrochemical feedstock has promoted refiners to seek methods of improving yields of these valuable products. The purpose of catalytic reforming is to convert a low-octane distillate fraction boiling within the gasoline range into high-octane blending stock and low aromatic hydrocarbons. The increase in the octane number of low-octane naphtha reformer feed can therefore be regardel as the transformation of naphthenes and paraffins into aromatics; resulting in the highest octane improvement. Paraffin and C,ring naphthene aromatization are guided by the metal and acid sites of bifunctional reforming catalyst. In order to obtain more information about the influence of hydrocarbon composition of naphtha reformer feed on the yield and research octane number of reformate, an experiment has been carried out to study the conversion of pure hydrocarbon (ie cyclohexane, methylcyclopentane and n.hexane); and naphthenes, and peraffins of three types of naphtha feeds with various hydrocarbon compositions using bifunctional reforming catalyst. The operating conditions: temperatures: 400 to 500 C, pressure: 10 to 30 bars and H/HC ratio = 8 mole/mole. A Catatest Unit operated in a continuous system was used in this experiment. Gas and liquid product samplers taken from gas and liquid samplers, respectively, were analyzed for their hydrocarbon using a Gas Liquid Chromatography.